2022
DOI: 10.31925/farmacia.2022.5.23
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Impact of the Compression Force by Evaluating the Mechanical and Release Properties of Mesalazine Tablets

Abstract: Drug delivery to the targeted site of action in the human body is always affected by the excipients used and almost in the same manner by some processing variables like changes in the compression force. The aim of this study was to investigate the impact of the changes in compression forces during tablet manufacturing on the mechanical and release properties of mesalazine matrix tablets. For the mechanical properties, hardness and friability were used as assessment properties, while dissolution test was undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Since the dissolution rate is also a function of the disintegration time of the tablets, we noticed a more coordinated and time-dependent (sustained) release of vitamin C from the spirulina + vitamin C tablets. These results are similar to those of Saurav A. et al, who found that good sized particles give more compact matrices, which slows down the dissolution rate of the active ingredient 15 . A prior granulation operation of the powder of formula A1 can improve its flow and its compressibility and will make it possible to obtain a firmer matrix which will slow down the rate of release of vitamin C.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Since the dissolution rate is also a function of the disintegration time of the tablets, we noticed a more coordinated and time-dependent (sustained) release of vitamin C from the spirulina + vitamin C tablets. These results are similar to those of Saurav A. et al, who found that good sized particles give more compact matrices, which slows down the dissolution rate of the active ingredient 15 . A prior granulation operation of the powder of formula A1 can improve its flow and its compressibility and will make it possible to obtain a firmer matrix which will slow down the rate of release of vitamin C.…”
Section: Discussionsupporting
confidence: 91%
“…The slight resistance of vitamin C tablets associated with spirulina could be explained by a better cohesion of the particles in the powder containing spirulina. Catalin D. et al, also demonstrated the influence of compression force, particle size and shape on tablets strength 15 . These parameters can be corrected by operations prior to compression such as the granulation and spheronization 14 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation